World literature, Kampala 1961-1968: literary circulation in Transition - Falk, Erik (Études littéraires africaines, 2019)
This article starts from two premises: that the almost exclusive reliance on the novel in several of the dominant elaborations of world literary models gives a very partial view of the global circulation of literature and, consequently, that much can be gained through analyses of complementary or alternative media and, secondly, that certain arguments within postcolonial literary studies on the circulation and audiences of African literature are inadequately grounded empirically. Taking the literary magazine Transition as an example – and more precisely its first, Ugandan, period –, this article seeks to make a contribution to both fields. Through discussion of the publication’s content and its circulation pattern, it shows that most of the authors published came from African countries, but also included British, American and Caribbean contributors; that poetry was its most represented literary genre, even as the magazine published seminal prose material; that the magazine’s readers, many of whom interacted actively, were found across the African continent and in Europe and the U.S.A.; and that Transition combined characteristics of « little » and « big » magazines. These empirical findings, the article argues, raise questions about key issues in world literary as well as postcolonial literary conceptualization – such as the status of the nation or the national field in world literary studies, the limitations of the notion of « literature » they use, and the relationship between (post-)colonial and « imperial » channels for production and circulation of literary artefacts.